2015
DOI: 10.1111/bph.13374
|View full text |Cite
|
Sign up to set email alerts
|

β‐Arrestin 2 dependence of δ opioid receptor agonists is correlated with alcohol intake

Abstract: BACKGROUND AND PURPOSEδ Opioid receptor agonists are being developed as potential treatments for depression and alcohol use disorders. This is particularly interesting as depression is frequently co-morbid with alcohol use disorders. Yet we have previously shown that δ receptor agonists range widely in their ability to modulate alcohol intake; certain δ receptor agonists actually increase alcohol consumption in mice. We propose that variations in β-arrestin 2 recruitment contribute to the differential behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
106
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 53 publications
10
106
1
Order By: Relevance
“…Besides a role in antinociception, DORs are implicated in alcohol consumption, depression and anxiety including alcohol withdrawal-induced anxiety (Filliol et al, 2000; Saitoh et al, 2004; van Rijn et al, 2010; Vergura et al, 2008). We and others have shown in preclinal animal models that the DOR-selective agonist TAN-67 can produce analgesia and reduce alcohol intake, depression and anxiety (Chiang et al, 2016; Kamei et al, 1995; van Rijn et al, 2010; van Rijn and Whistler, 2009). Hence, we were interested in investigating whether TAN-67, specifically, would alleviate AWiMA.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Besides a role in antinociception, DORs are implicated in alcohol consumption, depression and anxiety including alcohol withdrawal-induced anxiety (Filliol et al, 2000; Saitoh et al, 2004; van Rijn et al, 2010; Vergura et al, 2008). We and others have shown in preclinal animal models that the DOR-selective agonist TAN-67 can produce analgesia and reduce alcohol intake, depression and anxiety (Chiang et al, 2016; Kamei et al, 1995; van Rijn et al, 2010; van Rijn and Whistler, 2009). Hence, we were interested in investigating whether TAN-67, specifically, would alleviate AWiMA.…”
Section: Discussionmentioning
confidence: 95%
“…TAN-67 has frequently been labeled as a DOR1-selective agonist. The pharmacology underlying the subtypes is not well defined, but our data suggests that TAN-67 may interact with DOR-mu opioid receptor heteromers (van Rijn and Whistler, 2009) and have strong G-protein signaling bias, with limited efficacy for β-arrestin2 recruitment (Chiang et al, 2016). While our data would support DORs as a drug target for prevention but not treatment of AWiMA, it is important to consider that DOR agonists alleviate other components of the alcohol withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, these specific DOPr-mediated behaviors may be generated by a G protein-independent, arrestin-mediated signaling mechanism (Violin 2014). Previous studies demonstrated that DOPr activation leads to signaling through G protein-dependent and - independent pathways (Bradbury et al 2009; Charfi et al 2014; Charfi et al 2015); however, there are few reports connecting these distinct signaling mechanisms to specific behavioral outputs (Chiang et al 2016; Pradhan et al 2016). In conclusion, this study demonstrates that RGS4 differentially regulates SNC80-induced behaviors, suggesting that different molecular or cellular signaling pathways or neurocircuitry mediate these behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] As such, relatively few studies have systematically assessed this alternate pathway despite its important roles in regulating OR desensitization, and purported promotion of β-arrestin-dependent signal transduction through the scaffolding of various kinases. 15 An increasing number of studies have implicated δOR mediated β-arrestin recruitment with various (patho)physiological effects, ranging from tolerance, 16 alcohol intake 17,18 and δOR agonist-induced seizures. 16 To minimize these adverse effects, the development of "biased" ligands that can selectively activate the G protein pathway, without engaging the β-arrestinassociated pathways, 19 may provide a key set of pharmacological tools for reevaluating the drugability of δOR for several disease states.…”
Section: Introductionmentioning
confidence: 99%